Micropatterned coculture of vascular endothelial and smooth muscle cells on layered electrospun fibrous mats toward blood vessel engineering. Issue 6 (17th September 2014) - Li, Huinan; Liu, Yaowen; Lu, Jinfu; Wei, Jiaojun; Li, Xiaohong
Abstract A major challenge in vascular engineering is the establishment of proper microenvironment to guide the spatial organization, growth, and extracellular matrix (ECM) productions of cells found in blood vessels. In the current study, micropatterned fibrous mats with distinct ridges and grooves of different width were created to load smooth muscle cells (SMCs), which were assembled by stacking on vascular endothelial cell (EC)‐loaded flat fibrous mats to mimic the in vivo‐like organized structure of blood vessels. SMCs were mainly distributed in the ridges, and aligned fibers in the patterned regions led to the formation of elongated cell bodies, intense actin filaments, and expressions of collagen I and α‐smooth muscle actin in a parallel direction with fibers. ECs spread over the flat fibrous mats and expressed collagen IV and laminin with a cobblestone‐like feature. A z‐stack scanning of fluorescently stained fibrous mats indicated that SMCs effectively infiltrated into fibrous scaffolds at the depth of around 200 μm. Compared with SMCs cultured alone, the coculture with ECs enhanced the proliferation, infiltration, and cytoskeleton elongation of SMCs on patterned fibrous mats. Although the coculture of SMCs made no significant difference in the EC growth, the coculture system on patterned fibrous scaffolds promoted ECM productions of both ECs and SMCs. Thus, this patterned fibrous configuration not only offers a promising technology in the design of tissue engineering scaffolds to construct blood vessels with durable mechanical properties, but also provides a platform for patterned coculture to investigate cell–matrix and cell–cell interactions in highly organized tissues. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1949–1960, 2015.